VERIFIKASI DOSIMETRI ANISOTROPIC ANALYTICAL ALGORITHM (AAA) PADA TREATMENT PLANNING SYSTEM (TPS) ECLIPSE BERDASARKAN VARIASI MULTILEAF COLLIMATOR - Fadillah Ahmad; Afdhal Muttaqin; Dian Fitriyani; Ridwan Ridwan (Universitas Andalas, 2023)
Dosimetry verification of anisotropic analytical (AAA) algorithms based on variations of the multileaf collimator has been investigated using the Eclipse Treatment Planning System. This study used a 0.6cc ionization chamber farmer detector and Linac Clinical CX variant equipped with TPS Eclipse with AAA. This study used 6 MV energy and 2 Gy dose. The multileaf collimator was varied into six groups with the size (A, B, C, D, E, F) of the irradiation field used 20 cm x 20 cm. The measurement results were a dose deviation value or a dose ratio presentation in each irradiation area. The dose deviation of the multileaf collimator variation was A 0.86% for each group. Group B had 6.8%, Group C had -0.43%, Group D had 0.73%, Group E had 1.11%, and Group F had 0.84%. The mean dose deviation value for all multileaf collimator forms was 1.67%, where this value is within the tolerance value recommended by ICRU, namely 3-5%. The p-value in the Analysis of variance (ANOVA) for the entire group was 0.00. This data shows that there is no effect of variation in the multileaf collimator on the dose given.